Penerapan Algoritma Smith Pada Aplikasi Pencarian Anime Dalam Kumpulan Anime - Fansuri, Imam (TIN: Terapan Informatika Nusantara, 2020)
The development of the web is very advanced from year to year. The public is more interested in using the web because a variety of features can be displayed to meet user needs and appeal. The media with the most extensive network in the world (world wide web), is not limited by time and is not bound by regional boundaries. Media that is truly effective because it never stops operating and is always open to everyone around the world. For some people, anime is an entertainment to be seen. But sometimes they don't know all kinds of stories or the author of the stories. The solution that can be done is to create a web-based anime search system that can provide complete information about anime. By implementing the Smith search algorithm, where the Smith algorithm works is by doing 2 searches, namely the Preprocessing Phase and the Search Phase. By implementing the Smith algorithm in this web-based Anime search system, it is hoped that the search process for anime will be easier and faster. The system built is also very practical.